Hazard Maps and Probabilistic Failure Assessment: Two Ways of Tackling Reliability. (2015) - Muniz-Calvente, M.; Ramos, A.; Lamela, M.J.; Fernández-Canteli, A.
Abstract: Design: and lifetime prediction of structural and mechanical components require the assessment of the global probability of failure to be determined from stress and strain distributions obtained from FEM, as well as calculation of hazard maps in order to facilitate redesign and recognition of critical parts to be inspected regularly. The so-called generalized probabilistic approach (GPA), developed by the authors, allows the primary cumulative distribution function of failure (PCDFF) owning to a certain failure type to be determined for a certain material from experimental data and used subsequently for probabilistic prediction of static and fatigue failure in the design of industrial components. The approach ensures a realistic safety margin provided that the adequate GP (generalized parameter) and the corresponding failure criterion is properly recognized as a reference variable to be considered in the failure assessment. The way in which the results of such a reliability analysis are transmitted encompasses a variety of concepts under which failure can be understood and may be classified as global probability of failure and hazard maps, the former providing the conclusive failure probability for definitive design, and the latter representing, presumably, a risk of local failure that facilitates the possible redesign of the component but without providing the global probability of failure. In this work, an application is exemplary presented for the particular case of glass plates.